Відділ геології вугільних родовищ великих глибин: історія створення і розвитку - Безручко, К.А. (Геотехническая механика, 2012)
Изложена история создания и развития отдела геологии угольных месторождений больших глубин. Создание отдела – 1961 год. На первоначальном этапе он работал над проблемами прогноза горно-геологических условий разработки угольных месторождений, геологических условий и факторов выбросоопасности горных пород и угольных пластов. В дальнейшем проводилась работа по исследованию геологических условий формирования природных и техногенных скоплений метана в угольных пластах. History of creation and development of department of geology of coal deposits of large depths is expounded. Creation of department is 1961 year. On a primary stage he worked on problem of prognosis of forecasting mining and geological conditions of development of coal deposits, geological terms and factors of the troop landings of coal are a danger mountain breeds and coal layers. Work on research of geological terms of forming of natural and technogenical accumulations of methane in coal layers was conducted in future.